Phosphorus effects on growth and yield of groundnut varieties in the tropical savannas of northeast Nigeria - Kamara, A.Y.; Ekeleme, F.; Kwari, J.D.; Omoigui, L.O.; Chikoye, David (2011)
Groundnut production in northeast Nigeria is constrained by low level of soil phosphorus. This study evaluated four groundnut varieties for their response to P fertilization in two Nigerian agro-ecological zones (Sudan and Northern Guinea savanna) during 2005 and 2006. The experimental design was split plot with 0, 20, and 40 kg P ha–1 in the main plots and groundnut varieties (‘Samnut 22’, ‘local Wadabura’, ‘Samnut 21’, and ‘Samnut 23’) in the subplots. Pod yield increased linearly with increasing P rates in both years. Mean pod yield was higher by 49.3% at 20 kg and by 57.8% at 40 kg P ha–1 compared with unfertilized plots. ‘Samnut 23’ gave more grain yield than other varieties at both locations in 2005 and in Damboa during 2006. It is also an early maturing variety, and can thus be recommended to the farmers in Sudan savanna, which experiences short rainy seasons. However, for farmers interested in fodder production for livestock in addition to grain, the local variety, ‘Samnut 21’, and ‘Samnut 22’ are more appropriate.